Retraction Note: Relationship Between Multiple Sclerosis and Spiritual Distress - Çaksen, Hüseyin (Journal of Pediatric Epilepsy, 2023)
An investigation by the publisher found a number of articles, including this one, published in Journal of Pediatric Epilepsy in Volume 12, Number 03, 89-90, in September 2023 (DOI: 10.1055/s-0043-1764149), with a number of concerns, including but not limited to undeclared conflicts of interest and manipulated peer review procedures. As a result, the publisher has retracted and removed this article.